2007
DOI: 10.1007/s00726-007-0516-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue transglutaminase in tumour progression: friend or foe?

Abstract: Basic biological processes in which tissue transglutaminase (TG2, tTG) is thought to be important including apoptosis, cell adhesion and migration, ECM homeostasis and angiogenesis are key stages in the multistage tumour progression cascade. Studies undertaken with primary tumours and experimental models suggest that TG2 expression and activity in the tumour body and surrounding matrix generally decreases with tumour progression, favouring matrix destabilisation, but supporting angiogenesis and tumour invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 60 publications
2
31
0
Order By: Relevance
“…They are also consistent with the observation of increased tumour growth and progression of the B16 melanoma (F1and F6) in a mouse TG2 knockout model (Di Giacomo et al 2009;Jones et al 2006). Taking on board the proposed physiological functions for TG2 Griffin et al 2002) and those proposed for its roles in cancer progression (Kotsakis and Griffin 2007;Mehta 2009;Verma and Mehta 2007a), our next step was to Western blotting using specific antibodies as described in the ''Materials and methods''. The membranes were re-probed for a-tubulin detection as a standard for equal loading.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…They are also consistent with the observation of increased tumour growth and progression of the B16 melanoma (F1and F6) in a mouse TG2 knockout model (Di Giacomo et al 2009;Jones et al 2006). Taking on board the proposed physiological functions for TG2 Griffin et al 2002) and those proposed for its roles in cancer progression (Kotsakis and Griffin 2007;Mehta 2009;Verma and Mehta 2007a), our next step was to Western blotting using specific antibodies as described in the ''Materials and methods''. The membranes were re-probed for a-tubulin detection as a standard for equal loading.…”
Section: Discussionsupporting
confidence: 75%
“…Given these multifunctional roles of TG2, it is not surprising that reports have been contradictory as to whether TG2 is inhibitory to, or required for tumour progression (Grigoriev et al 2001;Hand et al 1988; Kotsakis and Griffin 2007;Verderio et al 1999). In recent studies, we demonstrated that the crosslinking activity of TG2 leading to ECM deposition and the inhibition of angiogenesis was sufficient for tumour growth blockade following intratumour injection of active TG2 into mice bearing CT26 colon carcinoma tumours (Jones et al 2006).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We also illustrated how this compensation mechanism is particularly important for cell survival during situations involving matrix remodeling (e.g. wounding and scarring, angiogenesis, and tumor metastasis), where high levels of TG2 and RGD peptides are released during the matrix remodeling process (23)(24)(25).…”
mentioning
confidence: 99%
“…We will now examine separately each of these instances, because it must be considered that these contrasting effects might be related by one side to the intrinsic different actions of Tgase2 as a signaling and a protein crosslinking enzyme, by the other to the toxic potential of transglutaminase itself, as well as to the reactive defense response by surrounding healthy tissues. These considerations are central for understanding the opposing effects of Tgase2 in disease pathogenesis as underlined for instance in the case of tumor biology (Kotsakis and Griffin 2007), as authors wonder whether Tgase is "friend or foe".…”
Section: The Pathology: Protective and Aggressive Actions Of Tgase2mentioning
confidence: 99%